2020
DOI: 10.1287/mnsc.2019.3511
|View full text |Cite
|
Sign up to set email alerts
|

Supply Chain Competition: A Market Game Approach

Abstract: We study supply chains where multiple suppliers sell to multiple retailers through a wholesale market. In practice, we often observe that both suppliers and retailers tend to influence the wholesale market price that retailers pay to suppliers. However, existing models of supply chain competition do not capture retailers’ influence on the wholesale price (i.e., buyer power) and show that the wholesale price and the order quantity per retailer do not change with the number of retailers. To overcome this limitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…Hsu et al (2019) study an MNF's decision about whether to supply a rival in the retail market by taking into account tax disparities between countries and regulations on transfer pricing. Using a market game approach, Korpeoglu et al (2020) analyze the role of tariffs in supply chain competition, expansion, and integration. Departing from the approaches of the above studies, our work will contribute to the field by assessing the impact of tariffs on the sourcing decisions of a manufacturer with a global supply chain structure and sales in multiple markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hsu et al (2019) study an MNF's decision about whether to supply a rival in the retail market by taking into account tax disparities between countries and regulations on transfer pricing. Using a market game approach, Korpeoglu et al (2020) analyze the role of tariffs in supply chain competition, expansion, and integration. Departing from the approaches of the above studies, our work will contribute to the field by assessing the impact of tariffs on the sourcing decisions of a manufacturer with a global supply chain structure and sales in multiple markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are several supply chain competition or operations economics models that do this (cf. Korpeoglu et al, 2020;Corbett and Karmarkar, 2001), but they include some assumptions that do not hold for medicine supply chains (e.g., demand is affected by price and indirectly by production quantities), analyze outcome variables other than availability, or study interventions/ decision variables that do not necessarily apply in the context of medicine supply chains. We therefore advocate that future researchers should develop models that capture 1) relevant interventions, 2) their impact on entry/exit decisions, and 3) the direct and indirect implications for supply chain risk.…”
Section: Agenda Item 3: Bringing the Government Perspective And Economics Into Supply Chain Risk Managementmentioning
confidence: 99%
“…It would be very helpful to have models that capture these decisions. Several general supply chain economics models are available (Corbett and Karmarkar, 2001;Korpeoglu et al, 2020), but they include some assumptions that do not hold for medicine supply chains. They also analyze outcome variables other than availability, or study interventions and decision variables that may not apply.…”
Section: Pathway Item 2: Studying the Comparative Cost-effectiveness Of Key Government Interventionsmentioning
confidence: 99%
“…Research on Supply Chain Game. Korpeoglu et al [1] studied supply chains in which multiple suppliers sell to multiple retailers in a wholesale market. ey found that integration may reduce the total profit of companies in a retailer-oriented supply chain.…”
Section: Research Reviewsmentioning
confidence: 99%